Participatory technology assessment for enhancing farming system productivity and developing entrepreneurship for sustainable livelihood - Pathak, P K; Pathak, K; Saikia, M; Saud, R K; Sarma, A; Borgohain, R; Kotoky, U; Borah, Nilay; Goswami, R; Barman, S; Das, A; Kalita, S; et al. (Indian Farming, 2022)
.